FENOMENA MODERN FATHERHOOD DAN IMPLIKASINYA TERHADAP MASALAH FATHERLESS DI INDONESIA: KAJIAN LITERATUR DALAM PERSPEKTIF KONSELING KELUARGA - Wistara Maharani Prashinta; Kireina Dewi Suyanto; Adelia Radinka Zahra; Oktavia Santoso; Ali Murtadho; Titin Indah Pratiwi (Program Studi Bimbingan dan Konseling, Universitas Negeri Jakarta, 2025)
Global social and economic changes have contributed to the transformation of fatherhood roles in many developed countries, giving rise to the Modern Fatherhood phenomenon characterized by fathers’ active involvement in childcare and emotional bonding. This model contrasts sharply with the condition of fatherlessness in Indonesia, where children frequently experience the absence of fathers physically or emotionally due to patriarchal norms, rigid gender roles, and limited work–family support. This study employs an analytical–comparative literature review to examine Modern Fatherhood as a representation of contemporary father involvement and compare it with Indonesia’s fatherless reality. The findings indicate that father engagement plays a crucial role in children’s emotional security, social development, and overall well-being. However, Indonesian fathers often face structural and cultural barriers that restrict active participation in childcare. Therefore, family counseling practices in Indonesia must adopt a father-inclusive approach that strengthens both economic and emotional caregiving roles. Such an approach can support healthier family dynamics and reduce the long-term risks associated with fatherlessness.